Pengaruh Pengendalian Internal Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan SPBU Di Wilayah Kabupaten Karanganyar, Jawa Tengah - Andayani, Lastri, Drs. Suyatmin Waskito Adi, M.Si (2016)
Employee performance is influenced by several factors, one of which is internal control as it is fundamental in governance to ensure governance objectives achieved effectively and efficiently. In addition, an ideal leader must have good leadership style, so it can improve the performance of employees. The purpose of this research is to determine the effect ofinternal control and leadership style on employees performance of gas station in the districts of Karanganyar. Research samples are 75 gas station employees by purposive sampling method. Data analysis in this study are multiple linear regression. The results showed that internal control and leadership style effecting onemployees performance. Keywords: internal control, leadership style, employees performance.